Bahasa Indonesia PENYESUAIAN DIRI DALAM KEGIATAN PEMBELAJARAN SMP NEGERI 27 SEMARANG DI MASA PANDEMI - Lisa Dewi Lestari; Siti Fitriana; Chr. Argo Widiharto Widiharto (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
The problem of this research is how to adjust to the learning activities of SMP Negeri 27 Semarang students during the Covid-19 Pandemic? The goal to be achieved in this study is to determine the level of adjustment in student learning activities. This type of research is qualitative with a phenomenological approach. Field observations were carried out by observing the object of research, namely students at SMP Negeri 27 Semarang. Field observations also collect documents in the form of student learning outcomes. The interview process was carried out with student and teacher sources. The data in this study were obtained through observation and interviews. The results of the analysis regarding adjustment in student learning activities during the pandemic showed a relationship between each superordinate theme, which appeared in more than half of the participants. The conclusion shows that the adjustment in learning activities of SMP Negeri 27 Semarang students during the Covid-19 pandemic is quite good. This is indicated by the behavior shown, such as seeking solutions, releasing emotions (catharsis) and seeking social support. Student adjustment is quite good because of the support from parents and friends and able to find solutions when experiencing problems in online learning. Students also show feelings of depression by releasing emotions. Suggestions that researchers can convey, BK teachers should be able to provide services that are in accordance with the conditions of students in order to overcome helping students make adjustments during learning both online and offline.